A rare association of Craniopharyngioma and Meyer-Rokitansky-Kuster-Hauser Syndrome in a patient with primary amenorrhea and delayed puberty – A Case Report - Shah, TP; Sah, PK; Mall, D; Karki, DB; Bajracharya, MR; Shrestha, PS; Wasti, K (Journal of Diabetes and Endocrinology Association of Nepal, 2025)
Background: Meyer-Rokitansky-Kuster-Hauser Syndrome (MRKH) is a congenital abnormality of the uterus and the upper two-thirds of the vagina in women showing normal development of secondary sexual characteristics with a normal karyotype of 46, XY. Craniopharyngioma is a rare intracranial neoplasm found in seller/suprasellar region with two distinct histologic phenotypes – adamantinoma Tous and papillary. It has insidious onset of symptoms and presents as headache, visual impairment and hormonal imbalances secondary to compression of adjacent pituitary manifesting commonly as sexual dysfunction in adults and growth failure in children. This case report presents a 20 years female with primary amenorrhea and absence of secondary sex characteristics, headache and visual field defect who was subsequently diagnosed as adamant nous craniopharyngioma with multiple pituitary hormones deficiency with Type 1 MRKH. Patient underwent transsphenoidal resection and replacement of levothyroxine and corticosteroid with further plan of reassessing pituitary gonadal axis, creation of a neovagina, addressing puberty induction and infertility (in vitro fertilization and surrogacy). It is too early to say that there may be an association between craniopharyngioma and MRKH. Whether craniopharyngioma and MRKH share a similar etiology is unclear. With increasing genetic testing, in the future, we may get some correlation.